Uninsured by Choice? A Choice Experiment on Long Term Care Insurance - Faical Akaichi; Joan Costa-Font; Richard Frank (Institute of Labor Economics (IZA), 2019)
We examine evidence from two unique discrete choice experiments (DCE) on long term care insurance and several of its relevant attributes, and more specifically, choices made by 15,298 individuals in the United States with and without insurance. We study the valuation of the following insurance attributes, namely daily insurance benefit, insurance coverage, the compulsory and voluntary nature of the insurance policy design, alongside the costs (insurance premium) and health requirements This paper investigates respondents' preferences and willingness to pay (WTP) for these care insurance's attributes using a random parameter logit model, and assess the heterogeneity of choice responses using demographic, socioeconomic and attitudinal motivations to segment response to insurance choices. We find that an increase in the insurance premium by an additional 100US would reduce insurance uptake by 1pp. Insurance policy uptake is higher when it provides benefits for the lifetime (the monthly marginal WTP being 178.64), and voluntary (the monthly marginal WTP increases by an extra 74.71) as opposed to universal, and when it forgoes health checks (the monthly marginal WTP increases by an extra 28US).
Keywords: I18; 330; self-insurance; constrained choices; long term care insurance; behavioural constraints; insurance design